THE IMPACT OF CURRICULUM CHANGES ON THE ROLE TEACHER IN SCHOOL - Nasution, Putra Thoip; Wahyuni, Atika (English Education Study Program FKIP Universitas Alwashliyah Medan, 2023)
Curriculum is a tool that is very important for the success of an education. The main purpose of curriculum is to prepare students to become intelligent, creative, innovative, faithful, and also affective when they are in the future society. As we know that in Indonesia there are always changes curriculum. This curriculum change definitely has an impact on the role of the teacher. This article will discuss about the impact of curriculum on the role teacher in school. Teachers are expected to implement the curriculum properly and correctly in the education system. This study aims to determine and describe the impact of curriculum changes on the role of teachers in school. The data was collected by library research.